PENERAPAN LEARNING ORGANIZATION DALAM MEWUJUDKAN MADRASAH RAMAH ANAK DI MTs AL-IHSAN - Lina Nurhasanah (Tatar Pasundan : Jurnal Diklat Keagamaan, 2019)
This study aims to find out how the application of the Learning Organization in realizing the Child Friendly Madrasah Program at MTs Al-Ihsan. This study uses kualitative approach with descriptive methods. Data collection techniques used observation techniques, interviews and documentation as well as source triangulation. While the data analysis technique uses interactive analysis; data collection, data reduction, data presentation and conclusion. The findings of this study revealed that it would be very difficult to realize the MRA program without the approach of Learning Organization discipline values developed by Peter Senge greatly helped MTs Al-Ihsan in launching the MRA program. LO disciplines are: 1) Personal Mastery, 2) Mental Models, 3) Share Vision, 4) Team Learning, and 5) System Thinking. MRA is based on the principles: 1). Non-discrimination; 2) The best interests of the child; 3). Life, survival and development; 4). Respect for children's views; and 5). Good management of madrasas. After evaluating for 3 (three) semesters, MTs Al-Ihsan is still in the process of developing further categories 2 of the 5 (five) categories of MRA designation established by KPPAP; 1). There is a policy to form an MRA development team, 2). Educators and trained personnel Child Rights, 3). Child participation, 4). Child-friendly learning process, 5). Complaints mechanism, 6). Have a safe / clean and healthy / caring and cultured / inclusive school program, 7). Parent participation, 8). Infrastructure and 9). Alumni participation. Obstacles to implementing the MRA program, namely; a) difficult to equate perceptions, b) difficulty translating the MRA program, c) limited facilities and infrastructure, d). Lack of support from the Ministry of Religion and e) the absence of the declaration of the KLA Program from the Regional Government. Key words: Implementation; Learning Organization; Child Friendly Madrasah